2017
DOI: 10.1080/10942912.2017.1315591
|View full text |Cite
|
Sign up to set email alerts
|

Anti-proliferative,in vitroantioxidant, and cellular antioxidant activities of the leaf extracts fromPolygonum minusHuds: Effects of solvent polarity

Abstract: The present study reports the antioxidant and anti-proliferative activities of Polygonum minus leaf extracts obtained through sequential extraction using four solvents of varying polarities (i.e. hexane (HX), ethyl acetate (EA), methanol, and water). The antioxidant potential was evaluated by measuring the total phenolic content (TPC), total flavonoid content (TFC), ferric reducing antioxidant power (FRAP), 2,2′-azinobis-3-ethylbenzothiazoline-6-sulphonic acid (ABTS) radical-scavenging, 1,1-diphenyl-2-picryl h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 52 publications
(78 reference statements)
4
19
0
Order By: Relevance
“…Secondary metabolites of the aromatic region (δ 5.50–9.00) were identified as quercetin, quercetin-3- O -rhamnoside [47,80], quercetin-3- O -glucoside [80], quercetin-3- O -glucuronide [81], quercetin-3- O -arabinofuranoside [47,80], rutin, myricetin derivatives, catechin, epicatechin, isorhamnetin, astragalin, apigenin, chlorogenic acid, gallic acid, coumaric acid, fumaric acid, formic acid, 3-methylxanthine and serotonin. Various studies have shown the presence of phenolic compounds and secondary metabolites, in particular flavonoids in P. minus leaves [82,83,84], as found also in this study.…”
Section: Resultssupporting
confidence: 88%
“…Secondary metabolites of the aromatic region (δ 5.50–9.00) were identified as quercetin, quercetin-3- O -rhamnoside [47,80], quercetin-3- O -glucoside [80], quercetin-3- O -glucuronide [81], quercetin-3- O -arabinofuranoside [47,80], rutin, myricetin derivatives, catechin, epicatechin, isorhamnetin, astragalin, apigenin, chlorogenic acid, gallic acid, coumaric acid, fumaric acid, formic acid, 3-methylxanthine and serotonin. Various studies have shown the presence of phenolic compounds and secondary metabolites, in particular flavonoids in P. minus leaves [82,83,84], as found also in this study.…”
Section: Resultssupporting
confidence: 88%
“…These compounds exhibit a wide range of pharmacological effects that are linked to their antioxidant properties. [10,11] Phenolic compounds have been reported to be excellent free radical scavengers due to their strong hydrogen-donating ability. [10,12] Reviewing the literature, nothing was reported concerning the phenolics of M. graeca (L.) Benth.…”
Section: Introductionmentioning
confidence: 99%
“…TPC and TFC of the plant are 388 mg GA/g and 423 mg QUE/g, respectively. Interestingly, TPC and TFC of P. pulchra were much higher (35) 0 (70) 0 (10) 0 (65) 437 ± 11 2 (75) 0 (70) 0 (10) 0 (65) 440 ± 9 0 (55) −2 (10) 0 (10) 0 (65) 449 ± 4 0 (55) 2 (130) 0 (10) 0 (65) 426 ± 14 0 (55) 0 (70) −2 (6) 0 (65) 504 ± 10 0 (55) 0 (70) 2 (14) 0 (65) 474 ± 14 0 (55) 0 (70) 0 (10) −2 (35) 461 ± 12 0 (55) 0 (70) 0 (10) 2 (95) 456 ± 13 0 (55) 0 (70) 0 (10) 0 (65) 534 ± 10 0 (55) 0 (70) 0 (10) 0 (65) 529 ± 9 0 (55) 0 (70) 0 (10) 0 (65) 536 ± 12 0 (55) 0 (70) 0 (10) 0 (65) 521 ± 14 0 (55) 0 (70) 0 (10) 0 (65) 529 ± 7 0 (55) 0 (70) 0 (10) 0 (65) 521 ± 12 0 (55) 0 (70) 0 (10) 0 (65) 528 ± 8 0 (55) 0 (70) 0 (10) 0 (65) 530 ± 7 0 (55) 0 (70) 0 (10) 0 (65) 532 ± 15 0 (55) 0 (70) 0 (10) 0 (65) 536 ± 7 0 (55) 0 (70) 0 (10) 0 (65) 522 ± 10 0 (55) 0 (70) 0 (10) 0 (65) 529 ± 9 than those of other plants in the Persicaria family, such as P. odoratum and P. minus [28,29]. The crude ethanolic extract of P. pulchra exhibited good inhibition of α-glucosidase with IC 50 of 33.53 ± 1.25 µg/mL, which is comparable to those of some anti-diabetic Vietnamese plants, like N. mirabilis, P. urinaria, and K. candel [30].…”
Section: Resultsmentioning
confidence: 99%